(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Young leaflets were used as the explants for in vitro regeneration of Albizia falcataria (L.) Fosberg without callus intervention. The leaf explants produced in vitro adventitious shoot buds directly on culturing with MS supplemented with BA, IBA (4.0/0.05 mg/l) and 10% coconut milk (v/v). Addition of casein hydrolysate and coconut milk increased the production of shoot buds. The buds produced shoots and roots and showed 66% survival in a field trial. This technique offers an effective way by which large number of genetically stable plants can be produced, maintained, multiplied and transported as disease free propagules or regenerants, safely and economically. Key words: Albizia falcataria, Leaf explant, Clonal propagation, Cytology D.O.I. 10.3329/ptcb.v20i1.5966 Plant Tissue Cult. & Biotech. 20(1): 63-72, 2010 (June)